System Dynamics of Toll Road Social Impacts: Causal Archetypes and Social Interaction in the Bakauheni – Terbanggi Besar Section - Marina, Bernaditha Catur; Putranto, Leksmono Suryo; Sulistyorini, Rahayu (Fakultas Teknik Universitas Tanjungpura, 2026)
Toll road development in Indonesia is a key driver of regional connectivity and economic growth, yet its social impacts are often complex and insufficiently captured by conventional evaluation methods. This study analyzes the dynamic social impacts of the Bakauheni–Terbanggi Besar Toll Road in Lampung Province using a system dynamics approach. Unlike prior impact assessments that rely on static indicators, this research explicitly models feedback interactions among social and economic variables through a Causal Loop Diagram (CLD). Data were obtained from literature review, policy documents, and regional socioeconomic indicators. The model groups variables into three interrelated clusters: mobility and accessibility, local economic activity, and social interaction. The results identify two reinforcing feedback loops linking improved accessibility to economic growth and investment to infrastructure expansion, and one balancing loop associated with agricultural land conversion and increased livelihood vulnerability. The analysis reveals that short-term economic gains may induce long-term social risks, including livelihood transformation and social inequality, if mitigation measures are not systematically integrated. These findings demonstrate the value of system dynamics for anticipating unintended social consequences of large-scale transport infrastructure projects.